Migração no município de Serra-ES no período de 2000 a 2010: uma análise a partir dos microdados dos censos demográficos do IBGE - Nascimento, Alexandre Holanda (2017)
This work investigates migration in Serra in the period 2000 - 2010. Microdata from the Brazilian Institute of Geography and Statistics (IBGE) were used in the criteria analysis and includes fixed-date migrants (those who declared their different towns of residence on the specific date of each census as compared to five years earlier), ancient migrants (those who lived for more than five years at the time of the census) and non-migrants (those who have always lived in the area). Aims at understanding the spatial redistribution and highlighting the main characteristics of migration, migrants their housings as well. Grounded on demographic perspective, this study encompasses geographic, historic and economic bias in its criteria analysis. It is thus, a contribution to the advance in understanding the impacts of migration towards demographic dynamics, spatial configuration of the researched area and its mains conditioning factors. Demography theoretical references were used to carry out the research in order to understand contributing and limiting factors and the main characteristics of migration. Provided that, theoretical references have been selected taking into consideration the constitution of Grande Vitória and Serra Metropolitan Regions (RMGV), and gives special emphasis to economic, urban, social and geographic factors, in an attempt to provide with a historical-contextualized analysis with recent past and contemporaneity. Furthermore, in an attempt to deepen the understanding such questions, statistics methodology has been adopted specially in relation to migrations and its variables, and also in reference to demography in general terms, most notably to natality and mortality rates. Concludes that the main reasons for both fixed date and ancient migrants in Serra are due to financial issues in municipal, state and metropolitan spheres and that migration was relevant for urban and economic growth in such spheres. It also concludes that service sector, industry and business were, respectively, the fields that most employed migrants and that their housing conditions are, in general terms, similar to the ones considered adequate internationally